Mit i dwoistość spojrzenia. Opozycje sacrum i profanum jako pozorna dysharmonia (na przykładzie wybranych filmów Jana Jakuba Kolskiego) - Otto, Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
The seemingly disharmonious image of the world presented in selected films by Jan Jakub Kolski is, in fact, fully ordered, coherent and internally consistent. This vision is structured by a broad interpretation of myth, particularly in its ontological and anthropological dimensions, as well as by the categories of the sacred and the profane – both in the Eliadean sense (sacred places and ritual objects) and in line with post-secular thought, which emphasizes the glorification of nature, the human body, and material objects. In the mythical reality constructed by the director, divine and pagan elements coexist on an equal footing, governed by proximity and parity.